Mentorship and ability grouping as barometers of socio-cognitive well-being among high ability students in Ibadan, Nigeria (2021)
This study examines the barometers of mentorship and ability grouping to social and cognitive well-being among students with superior academic performance in Ibadan, Nigeria, The study adopted a descriptive survey research design of correlational type. Purposive sampling technique was adopted in selecting schools in Ido and Ibadan Southwest Local Government Areas of Ibadan, with a total number of 215 high-ability students. Instruments utilized were: English Language and Mathematics Screening Test, Slosson Intelligence Test Revised Third Edition for Children and Adults (SIT- R3), Socio-cognitive Well-being Scale (r = 0.84), Mentoring Relationship Scale (r = 0.91) and Ability Grouping Scale (r = 0.78). Data were analysed, using Pearson Product Moment Correlation and Multiple Regression Analysis. Mentorship points to the high-ability students' socio-cognitive well-being (r = 641), n = 215, p(. 0001) <.05), ability group is also a pointer to socio-cognitive well-being among the students (r = .591, n = 215, p (.0001) <.05) while a joint contribution of mentorship and ability grouping to the socio-cognitive well-being of the students is also established (F(5, 12) = 87.686, = .673, p<.05). Mentorship and ability grouping have been advocated for inclusion into the existing curriculums as all relevant stakeholders in the study have been recommended to.